Batu Na Pir Sitinjak: Warisan Visual Batak Toba-Sebuah Tinjauan Hermeneutika - Sihombing, Marfenas Marolop; Nasution , Ikhwanuddin; Priyatno , Agus (Journal of Comprehensive Science, 2025)
This study examines Batu na Pir Sitinjak as a traditional Batak Toba art work that is rich in aesthetic, symbolic, and spiritual values. Batu na Pir not only functions as an ancestral tomb, but also as a visual representation of the Batak people's outlook on life, beliefs, and social structure. Using a traditional art theory approach, the elements of form, texture, and gorga ornaments are analyzed in relation to cosmological values that reflect the relationship between humans, ancestors, and the universe. Clifford Geertz's symbolism theory is used to interpret visual symbols that depict the structure of the upper, middle, and lower worlds. Meanwhile, Hans-Georg Gadamer's hermeneutic approach allows the reading of Batu na Pir as a living "visual text" that is open to dialogue across time and culture. The results of the study show that Batu na Pir Sitinjak is a cultural artifact that integrates aesthetic, ritual, and social functions, as well as being a medium of cultural communication that conveys the collective identity and noble values of the Batak Toba people. The preservation of these artifacts is important as an effort to maintain the sustainability of meaningful and dynamic visual cultural heritage.